Plasticized chitosan-PVA blend polymer electrolyte based proton battery - Majid, Siti Rohana; Arof, Abdul Kariem; Kadir, M.F.Z. (Elsevier, 2010)
This paper focused on the transport studies of PVA-chitosan blended electrolyte system and application in proton batteries. The electrolytes were prepared by the solution cast technique. In this work, 36 wt.% PVA and 24 wt.% chitosan blend doped with 40 wt.% NH(4)NO(3) exhibited the highest room temperature conductivity. The conductivity value obtained was 2.07 x 10(-5) S cm(-1). EC was then added in various quantities to the 60 wt.% [60 wt.% PVA-40 wt.% chitosan]-40 wt.% NH(4)NO(3) composition in order to enhance the conductivity of the sample. The highest conductivity obtained was 1.60 x 10(-3) S cm(-1) for the sample containing 70 wt.% EC. The Rice and Roth model was applied to analyze the conductivity enhancement. The highest conducting sample in the plasticized system was used to fabricate several batteries with configuration Zn//MnO(2). The open circuit potential (OCP) of the fabricated batteries was between 1.6 and 1.7 V. (C) 2009 Elsevier Ltd. All rights reserved.